Pemetaan Tingkat Bahaya Erosi Menggunakan Metode USLE di Desa Jatiarjo, Kecamatan Prigen, Kabupaten Pasuruan: Mapping of Erosion Hazard Levels Using the USLE Method in Jatiarjo Village, Prigen District, Pasuruan Regency - Krisna Ananta, Kevin; Widjajani, Bakti Wisnu; Siswanto, Siswanto (Agrocentrum, 2025)
The Erosion Hazard Level is one of the important indicators of land productivity capability in agriculture. This study was conducted from July to October 2023, aiming to determine the erosion hazard level (TBE) in Jatiarjo Village, Prigen District, Pasuruan Regency, using the Universal Soil Loss Equation (USLE) method implemented in a geographic information system (GIS) with the weighted overlay method. The research results show that the TBE in this area varies from very light to very heavy scales, with the location of Erosion Hazard Levels as follows: Very Low 87.64 ha, Low 410.25 ha, Medium 393.86 ha, High 205.06 ha, and Very High 453.53 ha. Shrubland has a very high erosion value compared to other land uses, as the shrub cover is not strong enough to withstand the rain energy, causing very high erosion.